Traditional Persian Medicine suggestions to Prevent Fasting Headache - Fatemeh Fadaei; Hossein .Rezaeizadeh (Tehran University of Medical Sciences, 2020)
Headache is one of the most common medical problems experienced by the majority of general population. In the latest version of the International Classification of Headache Disorders (ICHD-Ⅲ) beta in 2013, fasting headache, has been classified as a secondary headache, and a subheading of "Headache attributed to fasting". Suggested controversial hypothesis of this medical condition include associations with hypoglycemia, sleep quality and caffeine withdrawal, although these relationships have not been confirmed yet. The principal purpose of the present study is to review the etiology and proposed preventive and treating strategies regarding fasting headache in Persian Medicine (PM) literature. This complaint is regarded as a headache associated with dryness in PM. Therefore, words related to "dryness" from PM references.  Relevant keywords were also searched in modern medical literature and PubMed, Scopus, Google scholar, Web of science and Sid databases. Obtained results were subsequently compared following classification. Fasting plays a causative role in increasing heat in the heart, liver, and stomach (and other organs), and also decreasing body moisture. Therefore, the effective management as proposed by PM is reducing the heat and increasing body moisture. More research is needed to provide academic evidence in this regard.